2022
DOI: 10.1093/advances/nmac105
|View full text |Cite
|
Sign up to set email alerts
|

Flavan-3-ols and Cardiometabolic Health: First Ever Dietary Bioactive Guideline

Abstract: Guideline recommendation for a plant bioactive such as flavan-3-ols is a departure from previous recommendations as it is not based on deficiencies but rather improvement in health outcomes. Nevertheless, there is a rapidly growing body of clinical data reflecting benefits of flavan-3-ol intake that outweigh potential harms. Thus, the objective of the Expert Panel was to develop an intake recommendation for flavan-3-ols and cardiometabolic outcomes to inform multiple stakeholders including clinicians, policyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 64 publications
1
37
2
Order By: Relevance
“…Much of our work has indicated a beneficial impact of estimated dietary flavan-3-ol intake on CVD risk (23)(24)(25)(26)(27). This in alignment with the recent release of the first ever dietary bioactive guideline for flavan-3-ol intakes and cardiometabolic health (28). Most interestingly, the investigation of health outcomes utilizing PVLs as flavan-3-ol biomarkers has started to gain some traction.…”
Section: Discussionmentioning
confidence: 62%
“…Much of our work has indicated a beneficial impact of estimated dietary flavan-3-ol intake on CVD risk (23)(24)(25)(26)(27). This in alignment with the recent release of the first ever dietary bioactive guideline for flavan-3-ol intakes and cardiometabolic health (28). Most interestingly, the investigation of health outcomes utilizing PVLs as flavan-3-ol biomarkers has started to gain some traction.…”
Section: Discussionmentioning
confidence: 62%
“…They are found in various plant-based foods such as tea, cocoa, and berries [73]. Flavan-3-ols are well known due to their several health bene ts, such as improving cardiovascular health and reducing the risk of certain types of cancer [74]. Previous studies have also suggested that avan-3-ols may have antiviral activity [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Accumulating epidemiological evidence, most notably a recent large-scale randomized clinical study, have shown that flavan-3-ol intake can exert beneficial cardiovascular effects. [4][5][6] These reports supported the creation of dietary recommendations for the consumption of flavan-3-ols, [7] recognizing these bioactives as a valuable tool for primary prevention of cardiovascular disease and the promotion of healthy aging. After intake, flavan-3-ols are extensively transformed into a wide variety of metabolites that are thought to be the actual mediators of the beneficial effects observed after flavan-3-ol intake.…”
Section: Introductionmentioning
confidence: 99%